Syphilis screening in pregnancy in the United Kingdom, 2010–2011: a national surveillance study. (24th May 2016) - Townsend, CL; Francis, K; Peckham, CS; Tookey, PA
Abstract : Objective: To evaluate the national antenatal syphilis screening programme and provide evidence for improving screening and management strategies. Design: National population‐based surveillance. Setting: United Kingdom (UK). Population: All pregnant women screening positive for syphilis, 2010–2011. Methods: Demographic, laboratory and treatment details for each pregnancy were collected from UK antenatal units (~210), along with follow‐up information on all infants born to women requiring syphilis treatment in pregnancy. Main outcome measures: Proportion of women with newly or previously diagnosed syphilis among those with positive screening tests in pregnancy; proportion requiring treatment. Results: Overall, 77% (1425/1840) of reported pregnancies were confirmed syphilis screen‐positive. Of these, 71% (1010/1425) were in women with previously diagnosed syphilis (155 requiring treatment), 26% (374/1425) with newly diagnosed syphilis (all requiring treatment) and 3% (41/1425) required treatment but the reason for treatment was unclear. Thus 40% (570/1425) required treatment overall; of these, 96% (516/537) were treated (missing data: 33/570), although for 18% (83/456), this was not until the third trimester (missing data: 60/537). Follow up of infants born to treated women was poor, with at least a third not followed. Six infants were diagnosed with congenital syphilis; two mothers were untreated, three had delayed treatment and one had incomplete treatment (first trimester). Conclusion: Over 2 years, among pregnant women with confirmed positive syphilis screening results in the UK, a quarter had newly diagnosed infections and 40% required treatment. Despite high uptake of treatment, antenatal syphilis management could be improved by earlier detection, earlier treatment, and stronger links between healthcare teams. Tweetable abstract: 25% of pregnant women screening positive for syphilis in the UK were newly diagnosed and 40% needed treatment. Tweetable abstract: 25% of pregnant women screening positive for syphilis in the UK were newly diagnosed and 40% needed treatment.